Pengembangan Portal Tiket Pelanggan Terpadu untuk Meningkatkan Layanan Penyedia Jasa Internet PT. Padi Internet - Hariyanto Aditya Ramadhan; Desi Ramayanti (LPPM STIKI MALANG, 2024)
This study aims to develop an Integrated Customer Ticket Portal to enhance the service quality of the Internet Service Provider (ISP) at PT. Padi Internet. The background of this research is the need for an effective solution to manage customer complaints and improve service responsiveness. The research employs the waterfall methodology, which includes the stages of requirement analysis, system design, implementation, testing, and maintenance. Data collection techniques used include interviews with the customer service team, observation of operational processes, and documentation studies. The results of the study indicate that the development of the customer ticket portal can reduce response time to complaints, increase customer satisfaction, and provide useful analytical data for continuous service improvement. The implementation of this portal also results in a well-integrated system, facilitating ticket monitoring and management by the internal team. The practical implications of these findings are increased operational efficiency at PT. Padi Internet in handling customer complaints and further development of additional features that support better interaction with customers.